Microvesicles Derived from Inflammation-Challenged Endothelial Cells Modulate Vascular Smooth Muscle Cell Functions - Pan, Qunwen; Liu, Hua; Zheng, Chunyan; Zhao, Yuhui; Liao, Xiaorong; Wang, Yan; Chen, Yanfang; Zhao, Bin; Lazartigues, Eric; Yang, Yi; Ma, Xiaotang (Frontiers in Physiology, 2017)
Purpose: Microvesicles (MV) can modulate the function of recipient cells by transferring their contents. Our previous study highlighted that MV released from tumor necrosis factor-α (TNF-α) plus serum deprivation (SD)-stimulated endothelial progenitor cells, induce detrimental effects on endothelial cells. In this study, we investigated the potential effects of endothelial MV (EMV) on proliferation, migration and apoptosis of human brain vascular smooth cells (HBVSMC). Methods: EMV were prepared from human brain microvascular endothelial cells (HBMEC) cultured in a TNF-α plus SD medium. RNase-EMV were made by treating EMV with RNase A for RNA depletion. The proliferation, apoptosis and migration abilities of HBVSMC were determined after co-culture with EMV or RNase-EMV. The Mek1/2 inhibitor, PD0325901, was used for pathway analysis. Western blot was used for analyzing the proteins of Mek1/2, Erk1/2, phosphorylation Erk1/2, activated caspase-3 and Bcl-2. The level of miR-146a-5p was measured by qRT-PCR. Results:1) EMV significantly promoted the proliferation and migration of HBVSMC. The effects were accompanied by an increase in Mek1/2 and p-Erk1/2, which could be abolished by PD0325901; 2) EMV decreased the apoptotic rate of HBVSMC by approximately 35 %, which was accompanied by cleaved caspase-3 down-regulation and Bcl-2 up-regulation; 3) EMV increased miR-146a-5p level in HBVSMC by about 2 folds; 4) RNase-treated EMV were less effective than EMV on HBVSMC activities and miR-146a-5p expression. Conclusion: EMV generated under inflammation challenge can modulate HBVSMC function and fate via their carried RNA. This is associated with activation of theMek1/2 / Erk1/2 pathway and caspase-3/Bcl-2 regulation, during which miR-146a-5p may play an important role. The data suggest that EMV derived from inflammation-challenged endothelial cells are detrimental to HBVSMC homeostatic functions, highlighting potential novel therapeutic targets for vascular diseases.